9x+3=6x+75

Simple and best practice solution for 9x+3=6x+75 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+3=6x+75 equation:


Simplifying
9x + 3 = 6x + 75

Reorder the terms:
3 + 9x = 6x + 75

Reorder the terms:
3 + 9x = 75 + 6x

Solving
3 + 9x = 75 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
3 + 9x + -6x = 75 + 6x + -6x

Combine like terms: 9x + -6x = 3x
3 + 3x = 75 + 6x + -6x

Combine like terms: 6x + -6x = 0
3 + 3x = 75 + 0
3 + 3x = 75

Add '-3' to each side of the equation.
3 + -3 + 3x = 75 + -3

Combine like terms: 3 + -3 = 0
0 + 3x = 75 + -3
3x = 75 + -3

Combine like terms: 75 + -3 = 72
3x = 72

Divide each side by '3'.
x = 24

Simplifying
x = 24

See similar equations:

| 4x+1=x+52 | | 8x-7=3x+138 | | 2X^2-2AX+A^2-4=0 | | 7(4x-5)=-7 | | 57=19p | | 1/2x-2=1/2x-3/2 | | -8x-9=7x+36 | | Cos(2x)=Sin(5x-30) | | ln(15x)-20-ln(5)=3 | | 2y-9y=28 | | 10h=44 | | 2(a+3)+3(2a-4)=4(11-3a) | | 2x-2=-1+7 | | 12+4y+5y=48 | | ln(1)/ln(2) | | 7k-36=4k | | 8q/5-36=4k | | w-2/4=3 | | -4x-3=-1-4x | | x=5(2*3.14) | | (x/100)x20=63 | | d-3.03= | | 4.5+f= | | 6w^2-13w-6=0 | | 2x^3-3cosx=0 | | m-7= | | j+0= | | c=g+8 | | X=10+8y | | 3(x+y)=4x-5 | | b-28= | | 8-4x+x=20 |

Equations solver categories